Computational systems biology - Kriete, Andres; Eils, Roland (Elsevier, 2006)
I. Enabling Information and Integration Technologies for Systems Biology -- II. Foundations of Biochemical Network Analysis and Modeling -- III. Computer Simulations of Dynamic Networks -- IV. Multi-Scale Representations of Cells and Emerging Phenotypes